Parallel Yuan-Ming Yuan Imperial Garden: from digital twin garden to metaverse smart heritage park - Mengzhen KANG; Wenzhong QIU; Zifu CHEN; Meng WANG; Shasha XU; Xiujuan WANG; Aidong NI; Yujie JIANG; Shichao CHEN; Philippe DEREFFYE; Fei-Yue WANG (智能科学与技术学报)
Yuan-Ming Yuan Imperial Garden is a historically royal garden; it not only occupies an important position in the history of Chinese garden, but also enjoys a high reputation in the world.The historical and cultural values contained in Yuan-Ming Yuan Imperial Garden needs to be widely understood by the Chinese people and be remembered by the world through a new way.Focusing on the work policy for cultural relics of “protection first, strict management, mining value, rational utilization and good transmission”, a new solution of parallel Yuan-Ming Yuan Imperial Garden was proposed, which provided technical reference for the construction of the smart Yuan-Ming Yuan Imperial Garden.Parallel Yuan-Ming Yuan Imperial Garden is the application of ACP theory in the operation and management.Descriptive intelligence will be used to construct a virtual Yuan-Ming Yuan Imperial Garden, predictive intelligence will be used to conduct large-scale computational experiments in the virtual Yuan-Ming Yuan Imperial Garden, and prescriptive intelligence and parallel execution will be used to outbreak the geographical limit and lead to the smart management of Yuan-Ming Yuan Imperial Garden.It is expected that the development and enrichment of the Yuan-Ming Yuan Imperial Garden in the virtual world, and the increasingly parallel interaction and integration with the real world, will bring about a new operating mode.